The effectiveness of integrating classcraft: A gamified learning platform on enhancing writing skills among elementary school learners - Jayanti, Widya Mas Mardavam; Firdaus, Muhammad Yusuf; Arochman, Taufik (English Learning Innovation, 2024)
The objective of this study was to examine the influence of incorporating Classcraft, a gamified learning platform, on the writing abilities of elementary school students. The research employed a quantitative approach, utilizing a pre-test post-test control group design. Thirty second-grade elementary school pupils from a variety of schools participated. The paired sample t-test was employed to analyze the data that was collected through a written test. The results demonstrated a substantial disparity in the writing skills of the students who utilized Classcraft between the pre-test and post-test scores, suggesting that the gamified platform significantly improved their writing abilities. The results provide empirical evidence that supports the use of Classcraft as an educational intervention to enhance the writing proficiency of elementary students. The research posits that the integration of gamification through platforms such as Classcraft can establish a more engaging and pleasant learning environment, resulting in improved writing outcomes for young learners.